Effects of Ethnomathematics-Based Problem-Based Learning on Students’ Conceptual Understanding in Mathematics - Wikasari, Reni; Pardi, Habib Husnial; Negara, Habibi Ratu Perwira (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
This study investigates the effect of an ethnomathematics-based problem-based learning (PBL) model on students’ mathematical conceptual understanding. By integrating local culture into mathematics instruction, the model aims to facilitate more meaningful and contextual learning. A quantitative approach was employed using a quasi-experimental posttest-only control group design. Two classes were purposively selected: an experimental class with 20 students and a control class with 27 students, based on initial ability homogeneity and scheduling considerations. Data were collected through an essay test, developed from indicators of conceptual understanding, and supported by classroom observations. Data analysis involved prerequisite tests (normality and homogeneity) and hypothesis testing using the independent samples t-test. The results revealed a statistically significant difference between the experimental and control groups (p < 0.05), indicating that the ethnomathematics-based PBL model positively influences students’ conceptual understanding. These findings highlight the potential of integrating cultural contexts into problem-based learning to enhance students’ comprehension of mathematical concepts.